Bonsoir
Exercice 8
a) x^2 + 2x + 1 = (x)^2 + 2 * x * 1 + (1)^2
= (x + 1)^2
b) x^2 - 10x + 25 = (x)^2 - 2 * x * 5 + (5)^2
= (x - 5)^2
c) x^2 + 12x + 36 = (x)^2 + 2 * x + 6 + (6)^2
= (x + 6)^2
Exercice 9 :
a) x^2 - 81 = (x)^2 - 9^2 = (x - 9)(x + 9)
b) x^2 - 1 = (x)^2 - (1)^2 = (x - 1)(x + 1)
c) 9x^2 - 4 = (3x)^2 - (2)^2 = (3x - 2)(3x + 2)
Exercice 10 :
E = 4x^2 - 4x + 1
Factoriser E :
E = (2x)^2 - 2 * 2x * 1 + (1)^2
E = (2x - 1)^2
4x(x - 1) = 4x^2 - 4x
Non cela n'est pas correct. Elle n'a pas raison.